Status and Legal Consequences of Microchip Implantation with Emphasis on Civil Liability - Narges Dehghan; Reza Hosein Gandomkar; mohammad mahdi azizollahi (آموزه‌‌های فقه مدني, 2023)
Devices in the course of the evolution of science and technology continue to grow and develop for greater efficiency as well as being placed on smaller scales. The increasement use of microchips in the fields of medicine, services and etc. has caused a lot of concerns about the legal regulations of society and human about managing and control over this new technology, including license and legal effects of this technology. The use of this technology, especially its implantation in the human body for therapeutic purposes, from a jurisprudential and legal point of view, leads to consequences and liabilities for the person receiving the microchip, the physician and the factors that create or guide it. Microchips implantation in human and animal bodies is done for different purposes, but the invasion of human body is basically forbidden and illegitimate and the use of this technology and its disorders in legitimate cases may also cause injuries and damages to the receiver and others. Therefore, this article is a descriptive and analytical research method to describe this achievement and especially the civil liability caused by physical, mental and financial damages of its use and analyzes various assumptions of how to create legal liability.